Pengembangan Bahan Ajar Geografi Berbasisi Pendidikan Karakter pada Materi Lingkungan Hidup Kelas X - Iki Hariyad; Adhitya Prihadi; Rosanti (LPD IKIP PGRI Pontianak, 2023)
This research aims to carry out research and development to produce products and find out the feasibility of developing these products. The product produced is in the form of module teaching materials, namely geography teaching materials based on character education on environmental material. The problem formulation in this research is to determine the suitability of the teaching materials being developed. In this research, the test subjects were students of SMA Negeri 1 Embaloh Hlir, Kapuas Hulu Regency who were in class X with a total of 28 students. This research and development refers to the model according to Borg and Gall with research and development steps through 4 stages or what is called a 4-D model which has been modified into a 3-D model, namely defining, designing and developing in stages without carrying out stages. The final stage is the dissemination stage. The research instruments used were material and media expert validation as well as student response questionnaires to determine the suitability of teaching materials. This research produced teaching materials in the form of modules by obtaining a feasibility level from material experts of 80%, media experts of 78% and student responses of 83%.